Games to reinforce writing skills for very young learners. - Plaza Amaguaya, Leonela Mishelle (2023)
The research present the relationship between educational games and the type of English language learning style focused on writing skills in very young learners, establishing new learning strategies where students feel comfortable and interested in learning, being themselves the central axis of learning-teaching, thus being the games a didactic strategy. The type of research is the phenomenological study, and the applied method was qualitative. For this study, interviews were used as a technique of data collection. The population consisted of five teachers of the English area of three institutions in the city of Salinas: Escuela de Educación Básica Costa Azul, Escuela de Educación Básica El Barquito Del Saber, and Escuela de Educación Básica Pedro Maria Zambrano Reyes. The two study variables are divided into writing skills as the dependent variable and didactic games as the independent variable. After the data analysis, it was concluded that the games are a significant contribution as academic reinforcement for writing skills in very young learners.